2018
DOI: 10.4103/ccd.ccd_127_18
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anatomy and root canal morphology of the maxillary first molar using the cone-beam computed tomography among residents of the moscow region

Abstract: Background:The success of endodontic treatment depends on the knowledge of root canal system. The root canals have complex morphology and wide individual variations. The aim of this study was to evaluate the root canal morphology of the maxillary first molars among residents of the Moscow region using cone-beam computed tomography (CBCT) scanning.Materials and Methods:Three hundred CBCT images of patients aged 20–70 years old were analyzed to study the root canal system (the number of canals and the configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 19 publications
1
4
1
1
Order By: Relevance
“…Moreover, they used a similar methodology to determine the molar morphology. However, the proportion of the three roots in the current study was lower than the results of the study conducted in Moscow and Poland, where the prevalence of three roots was 100% (Olczak & Pawlicka, 2017;Razumova et al, 2018).…”
Section: Discussioncontrasting
confidence: 96%
“…Moreover, they used a similar methodology to determine the molar morphology. However, the proportion of the three roots in the current study was lower than the results of the study conducted in Moscow and Poland, where the prevalence of three roots was 100% (Olczak & Pawlicka, 2017;Razumova et al, 2018).…”
Section: Discussioncontrasting
confidence: 96%
“…The high percentage findings of a researcher also include Khademi et al 21 (79.2%). In addition, our findings were similar to Razumova et al 18 (59.8%). A study reported the lowest incidence rate as 36.3%, when examined worldwide.…”
Section: Discussionsupporting
confidence: 93%
“…[7][8][9][10][11] Studies evaluating the root canal complex of teeth have used various techniques, such as canal staining and clearing, radiographic examination, and physical sectioning. [12][13][14][15][16][17][18] Although clearing and physical sectioning techniques are the best way to analyze root canal anatomy, they are invasive modalities indicated only for extracted teeth. According to position statements of the American Academy of Oral and Maxillofacial Radiology and the American Association of Endodontics, an intraoral radiograph is accepted as a standard pattern of the imaging modality of endodontic diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A proper knowledge of root canal morphology is necessary for successful endodontic treatment (Alfawaz et al, 2019).The root canal system is complex and the canal may branch, divide and rejoin taking various pathways to the apex.Vertucci's established a proper method for differentiating root canal variations into the eight types.The classification has been widely used in several studies (Vertucci, Seelig and Gillis, 1974). As a group, the mandibular premolars are considered the most difficult teeth to treat endodontically and have high flare ups and high failure rates, as they have a high incidence of multiple roots or canals (Liu et al, 2013).Mandibular premolars may have extra root, not obvious in preoperative radiograph, challenging for shaping, cleaning, and obturation.Furthermore, the incidence, location, and morphology of root canal systems may vary in different ethnic or regional populations (Barakat et al, 2018;Alfawaz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%